Preparation method and application of macromolecular polylactic acid nano composite material based on copper-praseodymium metal organic framework
By adding copper pyramidol MOF nanoparticles and amino acids to polylactic acid materials, the problem of polylactic acid materials lacks versatility is solved, and the material's water vapor barrier, mechanical strength, light shielding, antibacterial and ammonia response discoloration performance is improved, and it is suitable for intelligent indicator materials and food storage monitoring.
Patent Information
- Application Number
- CN202411804270.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
Polylactic acid materials lack the functions of ammonia response, antibacterial, ultraviolet shielding, blue light shielding, etc., which limits its use in actual applications.
The polymer polylactic acid nanocomposite material based on the copper praseodymium metal organic frame is used to enhance the water vapor barrier, mechanical strength, toughness, ultraviolet shielding, blue light shielding, antibacterial and ammonia response discoloration properties of the material by adding copper praseodymium MOF nanoparticles and amino acids.
It has achieved the versatility improvement of polylactic acid materials, and has excellent water vapor barrier, mechanical properties, light shielding, antibacterial and ammonia response discoloration performance. It is suitable for intelligent indicator materials, especially in effectively indicating freshness changes during food storage.
Smart Images

Figure CN119708561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, and in particular to a preparation method and application of a polymer polylactic acid nanocomposite material based on a copper-praseodymium metal organic framework. Background Art
[0002] Polylactic acid is a new type of biodegradable material, made from starch raw materials from renewable plant resources (such as corn). Starch raw materials are saccharified to obtain glucose, which is then fermented with glucose and certain strains of bacteria to produce high-purity lactic acid, and then polylactic acid of a certain molecular weight is synthesized by chemical synthesis. It has good biodegradability and can be completely degraded by microorganisms in nature after use, eventually generating carbon dioxide and water without polluting the environment. This is very beneficial to protecting the environment. It is a recognized environmentally friendly material and has been widely used in food packaging materials. However, due to the lack of ammonia response, antibacterial, ultraviolet shielding, blue light shielding and other functions of polylactic acid materials, it is subject to certain restrictions in practical application. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method and application of a polymer polylactic acid nanocomposite material based on a copper-praseodymium metal organic framework. The composite material has excellent water vapor barrier, mechanical strength, toughness, ultraviolet shielding, blue light shielding, antibacterial, ammonia response color change and other properties, and can be used as an intelligent indicator material to timely and effectively indicate the freshness changes of seafood and meat products during storage. The preparation process of the composite material is simple, environmentally friendly, low-cost, and suitable for large-scale production.
[0004] To achieve the above object, the present invention provides a preparation method and application of a polymer polylactic acid nanocomposite material based on a copper-praseodymium metal organic framework, wherein the polymer polylactic acid nanocomposite material is composed of the following components in parts by weight: 100 parts of polylactic acid, 1-5 parts of copper-praseodymium MOF nanoparticles, and 3-8 parts of amino acids;
[0005] The specific steps of the preparation method of the polymer polylactic acid nanocomposite material are as follows:
[0006] Step 1, adding 80 parts of polylactic acid to 1000 parts of dioxane to prepare a uniform polylactic acid solution for standby use;
[0007] Step 2, dispersing 1-5 parts of copper-praseodymium MOF nanoparticles in 500 parts of dioxane to prepare a uniform dispersion of copper-praseodymium MOF nanoparticles for later use;
[0008] Step 3, adding the copper-praseodymium MOF nanoparticle dispersion obtained in step 2 to the polylactic acid solution obtained in step 1, stirring at 60° C. for 1 hour to obtain a uniform film-forming solution for standby use;
[0009] Step 4: pour the film-forming solution obtained in step 3 into a flat-bottomed glass dish and dry it to obtain a polylactic acid nanocomposite film having both antibacterial and ammonia response functions.
[0010] Preferably, in the above method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material, the condition for obtaining a uniform polylactic acid solution in step 1 is stirring at 60° C. for 2 hours.
[0011] Preferably, in the above method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material, the condition for preparing a uniform dispersion of copper-praseodymium MOF nanoparticles in step 2 is ultrasonic stirring at room temperature for 30 minutes.
[0012] Preferably, in the above method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material, the drying condition in step 4 is drying in an oven at 60° C. for 24 hours.
[0013] Preferably, in the above-mentioned method for preparing a polymer polylactic acid nanocomposite material based on copper-praseodymium metal, the method for preparing copper-praseodymium MOF nanoparticles comprises the following steps:
[0014] Step 1, dissolving copper nitrate and praseodymium nitrate in deionized water, adding lauric acid thereto, stirring and mixing uniformly to obtain a uniform blended solution;
[0015] Step 2, dissolving trimesic acid in N,N-dimethylformamide to obtain a trimesic acid solution;
[0016] Step 3, adding the trimesic acid solution obtained in step 2 to the mixed solution obtained in step 1, stirring and reacting at room temperature for 5 minutes, and then centrifuging, washing, and drying in sequence to obtain copper-praseodymium MOF nanoparticles.
[0017] Preferably, in the above-mentioned method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material, the weight parts of the various raw materials for preparing the blended liquid in step 1 are as follows: 3 parts of copper nitrate, 2 parts of praseodymium nitrate, 500 parts of deionized water, and 20 parts of lauric acid.
[0018] Preferably, in the above-mentioned method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material, the weight parts of the raw materials for preparing the trimesic acid solution in step 2 are as follows: 8 parts of trimesic acid and 500 parts of N,N-dimethylformamide.
[0019] Preferably, in the application of the above-mentioned copper-praseodymium metal-based polymer polylactic acid nanocomposite material, the prepared polymer polylactic acid nanocomposite material is used in food packaging, smart materials, biomedicine, antibacterial materials, ammonia detection, environmental monitoring and safety fields.
[0020] Therefore, the present invention adopts a preparation method and application of a polymer polylactic acid nanocomposite material based on a copper-praseodymium metal organic framework with the above structure. The prepared polylactic acid nanocomposite material, on the one hand, utilizes the synergistic effect of the complexing properties of copper ions and the electronic transition properties of rare earth praseodymium ions to enhance the color response performance of the composite material to ammonia; on the other hand, utilizes the antibacterial properties of amino acids and the properties of enhanced and toughened polylactic acid materials to obtain excellent water vapor barrier, mechanical strength, toughness, ultraviolet shielding, blue light shielding, antibacterial, ammonia response color change and other properties, which can be used as an intelligent indicator material to timely and effectively indicate the freshness changes of seafood and meat products during storage. The preparation process of the composite material is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has potential application value in food packaging, intelligent materials, biomedicine, antibacterial materials, ammonia detection, environmental monitoring and safety and other fields.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a scanning electron microscope image of copper-praseodymium metal organic framework-based polymer polylactic acid nanocomposite material and copper-praseodymium MOF nanoparticles involved in the preparation method and application thereof;
[0023] Figure 2 This is a scanning electron microscope image of the polylactic acid nanocomposite material prepared in Example 3 of the preparation method and application of a polymer polylactic acid nanocomposite material based on a copper-praseodymium metal organic framework of the present invention. DETAILED DESCRIPTION
[0024] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0026] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0027] The present invention uses polylactic acid as a matrix, and utilizes a copper-praseodymium metal organic framework nanoparticle and amino acids as functional fillers to improve the water vapor barrier, mechanical strength, toughness, ultraviolet shielding, blue light shielding, antibacterial, ammonia response color change and other properties of the polylactic acid material, to create a biodegradable polylactic acid nanocomposite material with both antibacterial and ammonia response functions, and to broaden its application in food packaging, intelligent materials, biomedicine, antibacterial materials, ammonia detection, environmental monitoring and safety and other fields.
[0028] In the following specific embodiments and comparative example formulations and preparation methods, the preparation method of the copper-praseodymium MOF nanoparticles comprises the following steps:
[0029] Step 1, dissolving 3 parts of copper nitrate and 2 parts of praseodymium nitrate in 500 parts of deionized water, adding 20 parts of lauric acid thereto, stirring and mixing uniformly to obtain a uniform blended solution;
[0030] Step 2, dissolving 8 parts of trimesic acid in 500 parts of N,N-dimethylformamide to obtain a trimesic acid solution;
[0031] Step 3: Add the trimesic acid solution obtained in step 2 to the mixed solution obtained in step 1, stir and react for 5 min at room temperature, then centrifuge, wash and dry in sequence to obtain copper-praseodymium MOF nanoparticles. (See the scanning electron microscope image for details) Figure 1 ).
[0032] Example 1
[0033] A polylactic acid nanocomposite material having both antibacterial and ammonia response functions, characterized in that it is composed of the following components in parts by weight: 80 parts of polylactic acid, 1 part of copper-praseodymium MOF nanoparticles and 4 parts of lysine.
[0034] The preparation method comprises the following steps:
[0035] (1) adding 80 parts of polylactic acid to 1000 parts of dioxane, stirring at 60° C. for 2 h to obtain a uniform polylactic acid solution for later use;
[0036] (2) dispersing 1 part of copper-praseodymium MOF nanoparticles and 4 parts of lysine in 500 parts of dioxane, stirring ultrasonically at room temperature for 30 minutes, and obtaining a uniform dispersion of copper-praseodymium MOF nanoparticles for later use;
[0037] (3) adding the copper-praseodymium MOF nanoparticle dispersion obtained in step (2) to the polylactic acid solution obtained in step (1), stirring at 60° C. for 1 h to obtain a uniform film-forming solution for standby use;
[0038] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed glass dish and dried in an oven at 60° C. for 24 h to obtain a polylactic acid nanocomposite film having both antibacterial and ammonia responsive functions.
[0039] Example 2
[0040] A polylactic acid nanocomposite material having both antibacterial and ammonia response functions, characterized in that it is composed of the following components in parts by weight: 80 parts of polylactic acid, 3 parts of copper-praseodymium MOF nanoparticles and 4 parts of lysine.
[0041] The preparation method comprises the following steps:
[0042] (1) adding 80 parts of polylactic acid to 1000 parts of dioxane, stirring at 60° C. for 2 h to obtain a uniform polylactic acid solution for later use;
[0043] (2) dispersing 3 parts of copper-praseodymium MOF nanoparticles and 4 parts of lysine in 500 parts of dioxane, stirring ultrasonically at room temperature for 30 minutes, and obtaining a uniform dispersion of copper-praseodymium MOF nanoparticles for later use;
[0044] (3) adding the copper-praseodymium MOF nanoparticle dispersion obtained in step (2) to the polylactic acid solution obtained in step (1), stirring at 60° C. for 1 h to obtain a uniform film-forming solution for standby use;
[0045] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed glass dish and dried in an oven at 60° C. for 24 h to obtain a polylactic acid nanocomposite film having both antibacterial and ammonia responsive functions.
[0046] Example 3
[0047] A polylactic acid nanocomposite material having both antibacterial and ammonia response functions, characterized in that it is composed of the following components in parts by weight: 100 parts of polylactic acid and 5 parts of copper-praseodymium MOF nanoparticles.
[0048] (1) adding 80 parts of polylactic acid to 1000 parts of dioxane, stirring at 60° C. for 2 h to obtain a uniform polylactic acid solution for later use;
[0049] (2) dispersing 5 parts of copper-praseodymium MOF nanoparticles and 4 parts of lysine in 500 parts of dioxane, stirring ultrasonically at room temperature for 30 minutes, and obtaining a uniform dispersion of copper-praseodymium MOF nanoparticles for later use;
[0050] (3) adding the copper-praseodymium MOF nanoparticle dispersion obtained in step (2) to the polylactic acid solution obtained in step (1), stirring at 60° C. for 1 h to obtain a uniform film-forming solution for standby use;
[0051] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed glass dish and dried in an oven at 60° C. for 24 h to obtain a polylactic acid nanocomposite film having both antibacterial and ammonia responsive functions.
[0052] Comparative Example 1
[0053] As a comparison standard of the above embodiments, the present invention provides a polylactic acid composite material prepared without copper-praseodymium MOF nanoparticles, comprising the following steps:
[0054] (1) adding 80 parts of polylactic acid to 1000 parts of dioxane, stirring at 60° C. for 2 h, and adding 4 parts of lysine to obtain a uniform polylactic acid solution for later use;
[0055] (2) adding 500 parts of dioxane to the polylactic acid and lysine solution obtained in step (1), stirring at 60° C. for 1 hour to obtain a uniform film-forming solution for standby use;
[0056] (3) The film-forming solution obtained in step (2) is poured into a flat-bottomed glass dish and dried in an oven at 60° C. for 24 h to obtain a polylactic acid composite material.
[0057] Comparative Example 2
[0058] As a comparison standard of the above embodiments, the present invention provides a polylactic acid composite material prepared without copper-praseodymium MOF nanoparticles, comprising the following steps:
[0059] (1) adding 80 parts of polylactic acid to 1000 parts of dioxane, stirring at 60° C. for 2 h to obtain a uniform polylactic acid solution for later use;
[0060] (2) adding 500 parts of dioxane to the polylactic acid solution obtained in step (1), stirring at 90° C. for 1 hour to obtain a uniform film-forming solution for standby use;
[0061] (3) The film-forming solution obtained in step (2) is poured into a flat-bottomed glass dish and dried in an oven at 60° C. for 24 h to obtain a polylactic acid composite material.
[0062] Structure and performance test:
[0063] The polylactic acid material prepared in the above comparative example and the polylactic acid nanocomposite material prepared in the embodiment were subjected to structure and performance tests, wherein the morphology of the polylactic acid nanocomposite material was characterized by a scanning electron microscope; the ultraviolet-visible performance was tested by an ultraviolet-visible spectrometer, and the average transmittance of ultraviolet rays (UVA, UVB, UVC) was calculated in accordance with GB / T18830-2009; the tensile performance was tested in accordance with GB / T1040-2006; the water vapor permeability coefficient was tested in accordance with ASTME96; the antibacterial property of the material was tested in accordance with QBT2591-2003; the ammonia response test method was as follows: the sample material was exposed to an ammonia environment, and the color change of the sample material was observed.
[0064] Shrimp freshness monitoring experiment: Fresh shrimps were purchased from the market, placed in a Petri dish, and sealed with a Petri dish cover. The polylactic acid material prepared in the comparative example and the polylactic acid nanocomposite material prepared in the embodiment (pre-cut into sample materials with a diameter of 1 cm) were attached under the cover. The shrimp samples were then stored in an oven at 25°C, and the changes in the freshness of the shrimps and the color changes of the sample materials were observed and recorded. The volatile basic nitrogen (TVB-N) values released by the shrimp samples during storage were tested according to the GB5009.288-2016 method.
[0065] The above performance test data are shown in Table 1 and Table 2.
[0066] Table 1 Sample performance test data
[0067]
[0068]
[0069] Table 2 Shrimp freshness monitoring experiment results (where t is the storage time of fresh shrimp)
[0070]
[0071]
[0072] The SEM results of the polylactic acid nanocomposites showed that the copper-praseodymium MOF nanoparticles can be evenly dispersed in the polylactic acid matrix, which means that the copper-praseodymium MOF nanoparticles and the polylactic acid matrix have good compatibility, which is conducive to obtaining polylactic acid nanocomposites with excellent performance.
[0073] The results of the ammonia response test experiment show that the polylactic acid materials prepared in Comparative Examples 1 and 2 are colorless and transparent. After being exposed to an ammonia environment, their colors do not change, and they still show colorless and transparent optical properties; the polylactic acid nanocomposite prepared in Example 1 is light blue, and after being exposed to an ammonia environment, its color changes to dark blue; the polylactic acid nanocomposite prepared in Example 2 is light blue, and after being exposed to an ammonia environment, its color changes to dark blue; the polylactic acid composite material prepared in Example 3 is blue, and after being exposed to an ammonia environment, its color changes to blue-black; this indicates that the polylactic acid nanocomposite prepared by the present invention has excellent ammonia response color change performance.
[0074] In summary, it can be seen from the sample performance test data (see Tables 1 and 2) that the polylactic acid nanocomposite material prepared by the present invention has excellent water vapor barrier, mechanical strength, toughness, UV shielding, blue light shielding, antibacterial, ammonia response color change and other properties, and can be used as an intelligent indicator material to timely and effectively indicate the freshness changes of shrimp and other meat foods during storage (see Table 2). The preparation process of the composite material is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has potential application value in food packaging, intelligent materials, biomedicine, antibacterial materials, ammonia detection, environmental monitoring and safety and other fields.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polymer polylactic acid nanocomposite material based on copper-praseodymium metal, characterized in that: The polymer polylactic acid nanocomposite material is composed of the following components in parts by weight: 100 parts of polylactic acid, 1-5 parts of copper-praseodymium MOF nanoparticles, and 3-8 parts of amino acids; The specific steps of the preparation method of the polymer polylactic acid nanocomposite material are as follows: Step 1, adding 80 parts of polylactic acid to 1000 parts of dioxane to prepare a uniform polylactic acid solution for standby use; Step 2, dispersing 1-5 parts of copper-praseodymium MOF nanoparticles in 500 parts of dioxane to prepare a uniform dispersion of copper-praseodymium MOF nanoparticles for later use; Step 3, adding the copper-praseodymium MOF nanoparticle dispersion obtained in step 2 to the polylactic acid solution obtained in step 1, stirring at 60° C. for 1 hour to obtain a uniform film-forming solution for standby use; Step 4: pour the film-forming solution obtained in step 3 into a flat-bottomed glass dish and dry it to obtain a polylactic acid nanocomposite film having both antibacterial and ammonia response functions.
2. The method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to claim 1, characterized in that: The condition for obtaining a uniform polylactic acid solution in step 1 is stirring at 60° C. for 2 hours.
3. The method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to claim 1, characterized in that: The conditions for preparing the uniform dispersion of copper-praseodymium MOF nanoparticles in step 2 are ultrasonic stirring at room temperature for 30 minutes.
4. The method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to claim 1, characterized in that: The drying condition in step 4 is drying in an oven at 60° C. for 24 hours.
5. The method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to claim 1, characterized in that: The preparation method of the copper-praseodymium MOF nanoparticles comprises the following steps: Step 1, dissolving copper nitrate and praseodymium nitrate in deionized water, adding lauric acid thereto, stirring and mixing uniformly to obtain a uniform blended solution; Step 2, dissolving trimesic acid in N,N-dimethylformamide to obtain a trimesic acid solution; Step 3, adding the trimesic acid solution obtained in step 2 to the mixed solution obtained in step 1, stirring and reacting at room temperature for 5 minutes, and then centrifuging, washing, and drying in sequence to obtain copper-praseodymium MOF nanoparticles.
6. The method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to claim 5, characterized in that: The weight parts of the raw materials for preparing the blended liquid in step 1 are as follows: 3 parts of copper nitrate, 2 parts of praseodymium nitrate, 500 parts of deionized water, and 20 parts of lauric acid.
7. The method for preparing a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to claim 5, characterized in that: The weight parts of the raw materials for preparing the trimesic acid solution in step 2 are as follows: 8 parts of trimesic acid and 500 parts of N,N-dimethylformamide.
8. The use of a copper-praseodymium metal-based polymer polylactic acid nanocomposite material according to any one of claims 1 to 7, characterized in that: The prepared polymer polylactic acid nanocomposites are used in food packaging, smart materials, biomedicine, antibacterial materials, ammonia detection, environmental monitoring and safety fields.
Citation Information
Patent Citations
Multifunctional polylactic acid nano composite material and preparation method thereof
CN113817301A
Tough carboxymethyl cellulose nano composite material with antibacterial and ammonia response functions as well as preparation method and application of tough carboxymethyl cellulose nano composite material
CN115260600A
Tough polyvinyl alcohol / starch composite film with antibacterial and ammonia-sensitive discoloration functions as well as preparation method and application of tough polyvinyl alcohol / starch composite film
CN117209932A
Composite of cellulose and inorganic porous coordination polymer, and production method of the same, composite of cellulose and metal organic framework, and production method of the same
JP2021116516A